2018
DOI: 10.2147/orr.s156449
|View full text |Cite
|
Sign up to set email alerts
|

The congenital clubfoot – immunohistological analysis of the extracellular matrix

Abstract: Purpose: Congenital clubfoot is one of the most common limb disorders in humans and its etiology is still unclear. In order to better understand the pathogenesis of patients with primary clubfoot, we examined whether there are quantitative changes in the extracellular matrix (ECM; based on common interstitial collagens [C] like CI and CIII, microfilamentous collagens like CVI, noncollagenous proteins like undulin, and enzymes like matrixmetalloproteinase [MMP]-2 and tissue inhibitor of matrixmetalloproteinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Older histological and electron microscopy studies have suggested the existence of fibrotic changes in tissue biopsies extracted from the clubfoot deformity- [13][14][15] . More recently published proteomic and molecular studies have revealed changes in the amount of collagen type I, III, VI, and profibrotic cytokines, such as transforming growth factor (TGF-β) and plateletderived growth factor (PDGF) in tissue from clubfoot medial side [16][17][18] and also in m. gastrocnemius 19 . These studies have therefore confirmed the presence of fibrosis in clubfoot.…”
Section: Introductionmentioning
confidence: 99%
“…Older histological and electron microscopy studies have suggested the existence of fibrotic changes in tissue biopsies extracted from the clubfoot deformity- [13][14][15] . More recently published proteomic and molecular studies have revealed changes in the amount of collagen type I, III, VI, and profibrotic cytokines, such as transforming growth factor (TGF-β) and plateletderived growth factor (PDGF) in tissue from clubfoot medial side [16][17][18] and also in m. gastrocnemius 19 . These studies have therefore confirmed the presence of fibrosis in clubfoot.…”
Section: Introductionmentioning
confidence: 99%
“…We found that MMP7, CASP3, and COL9A1 genes were involved in the progress of collagen formation and degradation of the extracellular matrix. In addition, interleukin-13 (IL-13) may induce myofibroblasts to produce ECM which indicates that excess stimulation induced by chronic inflammation promotes excessive accumulation of ECM [ 35 ]. These bioinformatics results supported the previous hypothesis that ECM abnormality and immune responses participated in the etiopathogenetic mechanism of clubfoot.…”
Section: Discussionmentioning
confidence: 99%
“…This area presents a rigid nature with hyperproduction of extracellular matrix components. 15 To fulfill the lack of prognosis, other possible methods to predict recurrence have been tested. Recently, a low eversor muscle activity has been considered as a significant recurrence parameter in CCF.…”
Section: Relapse and The Ponseti Methodsmentioning
confidence: 99%